The Second Known Species of the Recently Described Genus Keraunea (Convolvulaceae) - Lombardi, Julio Antonio (Phytotaxa, 2014)
This paper describes Keraunea  capixaba, the second known species of Keraunea (Convolvulaceae), native to the Brazilian Atlantic Rain Forest. It is easily distinguished from the only other known species of the genus by its almost complete hairlessness, bigger calyx and corolla lobes, longer corolla tube, and inflorescence type.